2014
DOI: 10.1107/s1399004714002788
|View full text |Cite
|
Sign up to set email alerts
|

A novel β-xylosidase structure fromGeobacillus thermoglucosidasius: the first crystal structure of a glycoside hydrolase family GH52 enzyme reveals unpredicted similarity to other glycoside hydrolase folds

Abstract: Geobacillus thermoglucosidasius is a thermophilic bacterium that is able to ferment both C6 and C5 sugars to produce ethanol. During growth on hemicellulose biomass, an intracellular β-xylosidase catalyses the hydrolysis of xylo-oligosaccharides to the monosaccharide xylose, which can then enter the pathways of central metabolism. The gene encoding a G. thermoglucosidasius β-xylosidase belonging to CAZy glycoside hydrolase family GH52 has been cloned and expressed in Escherichia coli. The recombinant enzyme ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Tx GH116 shows no structural similarity to other retaining β-glucosidases, which fall into families including GH1, GH2, GH3, GH5, and GH30 ( SI, Figure S2 ). Comparison to structures in the PDB database with PDBeFold 23 found that the Tx GH116 structure is most similar to the family GH52 β-xylosidase from Geobacillus thermoglucosidasius ( Gt GH52, PDB ID: 4C1O, 4C1P), 24 which upon global superposition yields an RMSD of 3.2 Å over 560 matched Cα atoms (PDBeFold Z score 8.3; SI, Figure S3A ). However, the sequence similarity of GH52 and GH116 is negligible (GH52 enzymes are not detected using PSI-BLAST with the Tx GH116 sequence as a search query), GH52 lacks the N-terminal loop that contributes to the entrance to the active site in GH116, and different numbers of strands are found in the major β-sheets of the N-terminal domain (see SI ).…”
Section: Resultsmentioning
confidence: 99%
“…Tx GH116 shows no structural similarity to other retaining β-glucosidases, which fall into families including GH1, GH2, GH3, GH5, and GH30 ( SI, Figure S2 ). Comparison to structures in the PDB database with PDBeFold 23 found that the Tx GH116 structure is most similar to the family GH52 β-xylosidase from Geobacillus thermoglucosidasius ( Gt GH52, PDB ID: 4C1O, 4C1P), 24 which upon global superposition yields an RMSD of 3.2 Å over 560 matched Cα atoms (PDBeFold Z score 8.3; SI, Figure S3A ). However, the sequence similarity of GH52 and GH116 is negligible (GH52 enzymes are not detected using PSI-BLAST with the Tx GH116 sequence as a search query), GH52 lacks the N-terminal loop that contributes to the entrance to the active site in GH116, and different numbers of strands are found in the major β-sheets of the N-terminal domain (see SI ).…”
Section: Resultsmentioning
confidence: 99%
“…Highlights from the available publications include the elucidation of the structural basis of the proinflammatory signalling complex mediated by TSLP (Verstraete et al, 2014); the crystal structure of the eukaryotic translation initiation factor eIF5B (399-852) from Saccharomyces cerevisiae (Kuhle & Ficner, 2014); the structure and thermodynamics of inhibition of Sporosarcina pasteurii urease (Benini et al, 2014); crystallographic structures of an active Spiegelmer, NOX-D20, bound to its physiological targets, mouse C5a and C5a-desArg (Yatime et al, 2015). Full MAD and Se-SAD capability are implemented as shown by the crystal structure of Geobacillus thermoglucosidasius GH family 52 xylosidase (Espina et al, 2014) solved with Se-SAD data, or by the in-house structure solution of glucose isomerase with a fluorescence scan around the Pb L III edge at 13050 eV (data not shown).…”
Section: Highlightsmentioning
confidence: 99%
“…The GH52 β-xylosidases are very similar to each other with amino acid sequence identities of around 41%–90%. In this family, crystal structures are available for β-xylosidases from Parageobacillus thermoglucosidasius TM242 (GT2_24_00240; PDB 4C1O; Figure 2i) [73] and G. stearothermophilus T-6 (Xyn52B2; PDB 4RHH) (Dann et al, unpublished work). With a sequence identity of 86%, the two proteins fold into almost the same structures; they display two distinct domains, an N-terminal β-sandwich domain and a C-terminal (α/α) 6 -barrel domain.…”
Section: Structural Diversity Of β-Xylosidasesmentioning
confidence: 99%
“…With a sequence identity of 86%, the two proteins fold into almost the same structures; they display two distinct domains, an N-terminal β-sandwich domain and a C-terminal (α/α) 6 -barrel domain. The catalytic residues of the GH52 enzymes, which are Glu-357 and Asp-517 in GT2_24_00240 [73], are located in the (α/α) 6 -barrel domain. Protein homology modeling based on the structure of GT2_24_00240 suggested that the domains are conserved among the GH52 β-xylosidases, except for the C-terminal domain of GsXylA.…”
Section: Structural Diversity Of β-Xylosidasesmentioning
confidence: 99%